How did that get in my lunchbox? : the story of food - Butterworth, Christine (Candlewick Press, 2011)
The best part of a young child's day is often opening a lunchbox and diving in. But how did all that delicious food get there? Who made the bread for the sandwich? What about the cheese inside? Who plucked the fruit? And where did the chocolate in that cookie get its start? From planting wheat to mixing flour into dough, climbing trees to machine-squeezing fruit, picking cocoa pods to stirring a vat of melted bliss, here is a clear, engaging look at the steps involved in producing some common foods. Healthy tips and a peek at basic food groups complete the menu.